REVITALISASI PERAN KARANG TARUNA MELALUI PEMBERDAYAAN SNS (SOCIAL NETWORKING SITES) (STUDI PADA KARANG TARUNA KECAMATAN PARDASUKA KAB. PRINGSEWU) (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This research background of the highest internet user in Indonesia is youth that isequal to 59% from all internet user in Indonesia. 80% of these young users access to socialmedia or Social Networking Sites (SNS). The use of SNS in a very fantasastic number byIndonesian youth, should be able to contribute to the existence of the organization of youth.The purpose of this research is to obtain description and analysis of the role of youth indeveloping young generation and also to empower SNS in revitalizing the role of youth indeveloping young generation in Pardasuka village. This type of research is descriptive, with aqualitative approach. The results of this study indicate that the role of Youth in developingyoung generation in Pardasuka sub-district, Pringsewu regency has not been limited to thetechnical role only. The youth also did not use SNS to revitalize the role of Karang Taruna dueto several inhibiting factors. Keywords: Revitalization, Karang Taruna, empowerment, Social Networking Sites (SNS)